Reform and Practice of Engineering Mechanics Courses in the Electrical Engineering Major in the Context of Engineering Education Accreditation - Li, Wenyong (International Journal of Mechanical and Electrical Engineering, 2024)
With the gradual promotion of Engineering Education Accreditation, the reform of the "Engineering Mechanics" course in the electrical engineering major is particularly urgent. Based on the background of Engineering Education Accreditation, this paper discusses the importance of the "Engineering Mechanics" course in the electrical engineering major, analyzes the shortcomings of the course setting and the new requirements brought by Engineering Education Accreditation, and proposes four main ideas for curriculum reform: strengthening the combination of theory and practice, dynamically updating course content, optimizing the school-enterprise cooperation model and establishing a diversified evaluation mechanism. Through the analysis of specific teaching cases, the effectiveness of these reform measures is verified, and corresponding response strategies are provided for the challenges that may be faced during the implementation process to ensure the effectiveness and sustainability of teaching reform. Finally, looking to the future, the importance of continuously promoting curriculum reform is emphasized to cultivate high-quality engineering talents that better meet the needs of the industry.